PENGARUH PEMBERDAYAAN DAN LEADER MEMBER EXCHANGE TERHADAP KINERJA KARYAWAN DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Untung Widodo; Lies Indriyatni; Susanti Wahyuningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study was conducted to analyze (1) How does the Empowerment of Self Efficacy? (2). How the influence of Leader Member Exchange (LMX) on Self Efficacy? (3). How does Empowering the Employee Performance (4). How the influence of Leader Member Exchange (LMX) against the Employee Performance? (5). How does Self Efficacy against Employee Performance? (6). How Self Empowerment Efficacy able to mediate the effect of the Employee Performance? (7). How Self Efficacy able to mediate the effect of LMX the Employee Performance ?. From the analysis conducted this study concluded that: 1) Empowerment positive effect on Self Efficacy. (2) Leader Member Exchange (LMX) positive effect on Self Efficacy. (3) Empowerment positive effect on employee performance. (4) Leader Member Exchange (LMX) positive effect on employee performance. and, (5) Self Efficacy positive effect on employee performance. (6) Self Efficacy able to mediate the effect of empowerment on employee performance. (7) Self Efficacy capable of mediating influence of the leader member exchange (LMX) on employee performance